Teachers’ Profile and Implementation of Kindergarten Program During Pandemic - Mostera, Marimar Jeremias; Digo, Gerry Sanez (FKIP Universitas Lampung, 2023)
Teacher’s profile and the implementation of kindergarten program during pandemic. Objectives: This study determined the profile of kindergarten teachers and status of the implementation of kindergarten program during the pandemic in Sorsogon, Philippines. Methods: This study employed the descriptive research method and utilized descriptive statistics for data analysis. Findings: The results of this study revealed that majority of kindergarten teachers are aged 31-40, female, married, bachelor’s degree holder, in-service for 6-10 years, teaching kindergarten for 1-5 years, and attended several related trainings. The overall average weighted mean as to resource, process, and outcome variables are 4.33, 4.43, and 4.59 respectively. Moreover, resource and process variable is “moderately observed” while outcome variable is “highly observed”. Conclusion: There is no significant relationship between teacher’s profile and status of the implementation of kindergarten program. Keywords: kindergarten program, pandemic, problem encountered, teacher’s profile.DOI: http://dx.doi.org/10.23960/jpp.v13.i1.202309